Pengaruh Ekstrak Jahe Merah (Zingiber Officinale) Terhadap Penurunan Nyeri Luka Post Sectio Saecarea Dan Percepatan Involusi Uteri Pada Ibu Post Sectio Saecarea Di Rumah Sakit Permata Bunda Malang - Ningrum, Novi Budi; Kuswandari, Eti; Aisyah, Fitria; Rahmawati, Mufida Annisa; Ummah, Wiqodatul (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Labor is the process of expulsion of the fetus that occurs at term pregnancy (37-42 weeks) born spontaneously with a back of the head presentation that takes place within 18 hours without complications for both mother and fetus. This process can be inconsistent with the theory so that the fetus can not be born normally due to several factors. So that medical action is needed in the form of a caesarean section. The action of giving birth to a mother with post sectio caesarea will feel pain in the suture wound in her abdomen which can affect physical and psychological conditions so that it can disrupt the process of uterine involution. The content of Red Ginger (Zingiber Officinale) is expected to reduce post sectio caesarea suture pain and minimize abnormalities in the uterine involution process. The purpose of this study was to determine the effect of red ginger extract (Zingiber Officinale) on reducing post sectio caesarea wound pain and accelerating uterine involution in post sectio caesarea mothers. . The design of this research is true experimental with the randomized pretest – posttest. In this study, 2 groups were used, namely the treatment group and the control group. The treatment group was given red ginger extract (Zingiber Officinale) and the control group was given a placebo. Data were analyzed using paired and independent t-test.